Numerical Simulation of Ferrofluid Flow in Heterogeneous and Fractured Porous Media Based on Finite Element Method - Huang, Tao; Liao, Xin; Huang, Zhaoqin; Wang, Renyi (Frontiers in Earth Science, 2021)
Ferrofluid is a kind of magnetic fluid, the flow of ferrofluid will be controlled by an external magnetic field. Based on this property, ferrofluid has caused the extensive concern in oil industry as a new function material. In this paper, the ferrofluid flow problem in complex porous media has been studied by numerical simulation, the validity and accuracy of the numerical algorithm are demonstrated through a 1-D horizontal tube example. At last, the effect of magnetic force on ferrofluid flow in complex porous media such as heterogeneous and fractured porous media are investigated. The results show that there is basically no flow in low permeability or secondary fracture without magnetic field. However, the ferrofluid flow velocity and domain can be changed by applying an external magnetic field. This novel phenomenon may provide a new idea for enhance oil recovery or other industrial purposes by using ferrofluid.